Effect of growth regulators on vegetative propagation of guayusa (Ilex guayusa L.) - Muñoz López, Carmen Emelia; García García, Lisseth Mishel; Medina Litardo, Reina Concepción; Vivas Vivas, Leticia (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
The study was carried out in the province of Esmeraldas, Canton Quinindé in the El Limón enclosure, the effect of growth regulators for the vegetative propagation of guayusa (Ilex guayusa) was evaluated. We studied 3 treatments (Auxins): ANA (2.75 and 5.50mg/l) and AIB (10.00 mg/ha) generating 3 treatments with 7 repetitions, the design was used completely randomly, with 5% of probability of the Duncan test (Analysis of variance). ). According to the results obtained in the present research, the following is concluded: Naphthaleneacetic acid at doses of 2.75 mg / l and 5.50% presented an average of 85% both, Indolbutyric acid with 72%; Naphthaleneacetic acid at doses of 2.75 mg/l reported the highest root volume and length with an average of 4.2 mg/l and 7.76 mm respectively.
Keywords: Regulators; growth; air layering; naphthaleneacetic acid; indolebutyric acid